Berberine ameliorates cartilage degeneration in interleukin‐1β‐stimulated rat chondrocytes and in a rat model of osteoarthritis via Akt signalling. Issue 2 (28th November 2013) - Zhao, Honghai; Zhang, Tongen; Xia, Chun; Shi, Lei; Wang, Shaojie; Zheng, Xinpeng; Hu, Tianhui; Zhang, Bing
Abstract Berberine, a plant alkaloid used in Chinese medicine, has broad cell‐protective functions in a variety of cell lines. Chondrocyte apoptosis contributes to the pathogenesis of cartilage degeneration in osteoarthritis (OA). However, little is known about the effect and underlying mechanism of berberine on OA chondrocytes. Here, we assessed the effects of berberine on cartilage degeneration in interleukin‐1β (IL‐1β)‐stimulated rat chondrocytes and in a rat model of OA. The results of an MTT assay and western blotting analysis showed that berberine attenuated the inhibitory effect of IL‐1β on the cell viability and proliferating cell nuclear antigen expression in rat chondrocytes. Furthermore, berberine activated Akt, which triggered p70S6K/S6 pathway and up‐regulated the levels of aggrecan and Col II expression in IL‐1β‐stimulated rat chondrocytes. In addition, berberine increased the level of proteoglycans in cartilage matrix and the thickness of articular cartilage, with the elevated levels of Col II, p‐Akt and p‐S6 expression in a rat OA model, as demonstrated by histopathological and immunohistochemistry techniques. The data thus strongly suggest that berberine may ameliorate cartilage degeneration from OA by promoting cell survival and matrix production of chondrocytes, which was partly attributed to the activation of Akt in IL‐1β‐stimulated articular chondrocytes and in a rat OA model. The resultant chondroprotective effects indicate that berberine merits consideration as a therapeutic agent in OA.